More about Thraulodes Ulmer, 1920 (Ephemeroptera: Leptophlebiidae) from the Brazilian Amazonia: three new species, a new record and a gynandromorph report - Do Nascimento, Jeane Marcelle Cavalcante; Castelaci , Luciana Camurça; Hamada, Neusa (Zootaxa, 2021)
Three new species of Thraulodes Ulmer (Ephemeroptera: Leptophlebiidae) from Brazilian Amazonia are described: Thraulodes yara n. sp., Thraulodes yaciara n. sp. and Thraulodes ykamiaba n. sp., all based on imagoes. All three new species can be easily recognized by general color pattern and genitalia morphology. Thraulodes alboniger Kluge, 2020, known only from Peru, is recorded in Brazil. A remarkable gynandromorph case is presented for T. yara n. sp.